Calcium Hydroxide – A Great Calcific Wall - Khan, Sheeba; Inamdar, Nasir K.; -, Akash; Meshram, GK; Singh, MP; Chaurasia, Hemanth (Journal of Orofacial Research, 2011)
Calcium hydroxide is a material which has been used for a variety of purposes. The precise mechanism by which it acts is still not clearly understood. This paper gives a brief review on different applications of Calcium Hydroxide and its mechanism of action.